1985
DOI: 10.1080/00365518509160968
|View full text |Cite
|
Sign up to set email alerts
|

[3H]ouabain binding and sodium content in lymphocyte sub-populations and the demonstration of increased binding in type 2 diabetes mellitus

Abstract: The number of specific [3H]ouabain binding sites in T-lymphocytes was determined and linear Scatchard plots were obtained. The number of sites was 30088 +/- 3039 (mean +/- SD) per lymphocyte in 14 healthy males and 33939 +/- 3185 in 11 males with type 2 diabetes (P less than 0.01). No difference between the dissociation constants were found (Kd = 3.91 and 3.86 mmol/l). The number of binding sites in lymphocytes from 15 healthy males with normal glucose tolerance but with a strong family history of type 2 diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A detailed questionnaire was answered by the parents of the obese children. We analyzed red cell Na-K-ATPase activity by the 3H-Oubain binding method, and measured intracellular N a + , K + and plasma Mg2+ and HPO~- (2,3).…”
Section: Childhood Obesity: Plasma Potassium and Na-k-atpase Indicate...mentioning
confidence: 99%
“…A detailed questionnaire was answered by the parents of the obese children. We analyzed red cell Na-K-ATPase activity by the 3H-Oubain binding method, and measured intracellular N a + , K + and plasma Mg2+ and HPO~- (2,3).…”
Section: Childhood Obesity: Plasma Potassium and Na-k-atpase Indicate...mentioning
confidence: 99%
“…Hypertensive individ-uals have elevated levels of intracellular sodium [Hilton, 19861, probably owing to an abnormality in the sodium pump; Blaustein [ 19771 proposed a hypothesis relating sodium transport to blood pressure regulation. Berntorp et al [1985] found high sodium pump activity in diabetics, which may relate to stimulation of the sodium pump by insulin [Moore, 19831. The sodium pump consists of the enzyme Na' K' ATPase, which exchanges internal sodium for external potassium ions [Sweadner and Goldin, 19801. The sodium pump is selectively inhibited by ouabain, facilitating measurement of its activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, obese subjects frequently do not exhibit reduced sodium pump activity [Ash et al, 1983;Beutler et al, 1983;Charalambous et al, 1984a;Miilunpalo et al, 1985;Simat et al, 1983;Webster et al, 19841, al-though the fault might lie in the inadequacy of erythrocytes as surrogates for highenergy-consuming cells [Charalambous et al, 1984b;Welle, 19891. Likewise, the sodium transport alterations reported for diabetic patients lack consistency [Bemtorp et al, 1985;Finotti and Palatini, 1986;Nagamatsu et al, 1986;Chimori et al, 19891. Of the three diseases, hypertension associates most consistently with sodium transport abnormalities [Rutherford et al, 19921. Garay [1990] lists five sodium transport abnormalities contributing to hypertension; the abnormalities include decreased affinity for internal sodium of the sodium-potassium pump and sodium-potassium cotransport and increased maximal rates of sodium-potassium cotransport, sodium-lithium countertransport, and passive sodium permeability.…”
Section: Introductionmentioning
confidence: 99%